Safety and Effectiveness of a Biosimilar Recombinant Human Growth Hormone in Children Requiring Growth Hormone Treatment: Analysis of Final Data from PATRO Children, an International, Post-Marketing Surveillance Study - Loche S; Kanumakala S; Backeljauw P; Schwab KO; Lechuga-Sancho AM; Esmael A; Urosevic D; Boldea A; Zabransky M (Dove Medical Press, 2024)
Sandro Loche,1 Shankar Kanumakala,2 Philippe Backeljauw,3 Karl Otfried Schwab,4 Alfonso M Lechuga-Sancho,5- 7 Altaher Esmael,8 Dragan Urosevic,9 Anca Boldea,8 Markus Zabransky8 1Endocrinologia Pediatra e Centro, Screening Neonatale, Ospedale Pediatrico Microcitemico "A. Cao", Cagliari, Italy; 2University Hospitals Sussex NHS Trust, Royal Alexandra Children's Hospital, Brighton, UK; 3Cincinnati Children's Hospital Medical Center, University of Cincinnati College of Medicine, Cincinnati, OH, USA; 4Department of Pediatrics, University Medical Center, Freiburg, Germany; 5Servicio de Pediatría, Hospital Universitario Puerta del Mar, Cádiz, Spain; 6Departamento Materno Infantil y Radiología, Universidad de Cádiz, Cádiz, Spain; 7Instituto de Investigación e Innovación Biomédica de Cádiz (INiBICA), Cádiz, Spain; 8HEXAL AG (a Sandoz company), Holzkirchen, Germany; 9Novartis Sandoz Biopharmaceutical AG, c/o HEXAL AG, Basel, SwitzerlandCorrespondence: Sandro Loche, Endocrinologia Pediatra e Centro, Screening Neonatale, Ospedale Pediatrico Microcitemico "A. Cao", Via Jenner, 09121 Cagliari, Italy, Email sandroloche@libero.itPurpose: Omnitrope® (somatropin) was approved as a biosimilar recombinant human growth hormone (rhGH) in 2006. Here, we report final data from the PAtients TReated with Omnitrope® (PATRO) Children study, a post-marketing surveillance study designed to monitor the long-term safety and effectiveness of this treatment in pediatric patients.Methods: The study population included all pediatric patients treated with Omnitrope® (biosimilar rhGH), administered via daily injection, in routine clinical practice. The primary objective was to assess long-term safety, with effectiveness assessed as a secondary objective.Results: In total, 7359 patients were enrolled and treated in the PATRO Children study; 86.0% were treatment-naïve at baseline. Growth hormone deficiency was the most frequent indication (57.9%), followed by patients born small for gestational age (SGA; 26.6%). The mean (SD) duration of exposure to biosimilar rhGH was 3.66 years (2.39). A total of 16,628 adverse events (AEs) were reported in 3981 (54.1%) patients, most of which were mild/moderate. AEs suspected to be treatment related occurred in 8.3% of patients, most frequently headache (1.6%), injection-site pain (1.1%), or injection-site hematoma (1.1%). The incidence rate (IR) of type 2 diabetes mellitus was 0.11 per 1000 person-years (PY) across all patients, and 0.13 per 1000 PY in patients born SGA. The IR of newly diagnosed primary malignancies was 0.22 per 1000 PY across all patients. In the 6589 patients included in the effectiveness population, a sustained catch-up growth was observed across all indications. After 5 years of treatment, height SDS increased from baseline by a median (range) of +1.79 (- 3.7 to 6.2) in treatment-naïve patients and +0.73 (- 1.4 to 3.7) in pretreated patients.Conclusion: This final analysis of the PATRO Children study indicates that biosimilar rhGH is well tolerated and effective in real-world clinical practice. These data are consistent with the well-characterized safety profile of rhGH treatment in pediatric patients.Plain Language Summary: Why was the study done?Injections of growth hormone medicine can be used to increase height velocity in children with growth disorders.It is important to monitor the safety of long-term growth hormone treatment, especially regarding the risk of cancer and diabetes.What did the researchers do?PATRO Children was a study designed to look at the safety of using a growth hormone medicine for long periods of time.This study included children with several different growth disorders who were treated with a growth hormone medicine called Omnitrope®, which is administered via daily injections, and followed them throughout their treatment.The researchers aimed to evaluate the risk of specific safety concerns in these patients, including cancer and diabetes.What did the researchers find?A total of 7359 patients were enrolled from 304 sites around the world.Overall, 8.3% of patients had an adverse reaction that was considered to be related to growth hormone treatment.The most common adverse reaction considered related to growth hormone was headache, which occurred in 1.6% of patients.The risk of developing diabetes and cancer was low and comparable to what has been seen in previous studies in patients treated with growth hormone, and in the general population.What do the findings mean?The adverse reactions seen in this study were consistent with the well-characterized safety profile of growth hormone treatment in pediatric patients. This supports previous studies showing growth hormone treatment is not associated with an increased risk of cancer or diabetes in children.Keywords: Omnitrope, PATRO Children, growth hormone, pediatrics, growth hormone deficiency, small for gestational age